Assessing Grammatical Cohesive Devices in the Findings and Discussion of Research Articles by Graduate Students - Khasanah Palupi Akbar; Januarius Mujiyanto; Djoko Sutopo (English Education Journal, 2022)
Writing research articles is a 'tradition' conducted by students in every learning activity in higher education. This study aimed to analyze the use of grammatical cohesive devices found in the findings and discussion of research articles written by graduate students of English Education. Discourse analysis was employed as the research design and a descriptive qualitative approach was utilized to elaborate the analysis. Qualitative data in the form of text consisting of sentences and clauses containing cohesion were the primary data in this research. The data were obtained through observation and documentation by conducting a preliminary study, collecting the research articles, and verifying the data. The data were analyzed by identifying, classifying, describing, and drawing conclusions. The results of the study showed that the students employed all four types of grammatical cohesive devices in the findings and discussion of research articles. The most dominant grammatical cohesive device utilized by the students was reference and conjunction with total use of 2367 and 955 respectively. There was an apparent margin gap between the dominantly used devices and the least employed devices as there were only 5 occurrences of substitution and 12 occurrences of ellipsis. In conclusion, the students preferred to use only two types of grammatical cohesive devices while neglecting the utilization of the other types. Moreover, this study will hopefully provide suggestions for students on how to use grammatical cohesive devices and additional guides for teachers in teaching students on how to compose a well-organized research paper.